2019
DOI: 10.1039/c9tc04911h
|View full text |Cite
|
Sign up to set email alerts
|

Order–disorder transformation of intercalated cations triggering huge negative thermal expansion, switchable dielectrics and ion conduction near room temperature in a 2D vanadium oxide hybrid

Abstract: A 2D vanadium oxide hybrid crystal shows an order–disorder phase transition at ∼328 K/316 K upon heating/cooling, which triggers huge negative thermal expansion, switchable dielectrics and ion conduction near room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The results of our prediction showed that the classifier works well since most of the circles are located on the diagonal line (Figure right). The averaged oxidation state is correctly predicted in 34 out of 61 crystal structures; for example, oxidation states V, IV, V, and IV were correctly predicted for the V(1), V(2), V(3), and V(4) atoms in (C 3 H 12 N 2 )­[V 4 O 10 ] (ZOLJEP06), which correspond to the values specified in the original paper.…”
Section: Resultsmentioning
confidence: 58%
“…The results of our prediction showed that the classifier works well since most of the circles are located on the diagonal line (Figure right). The averaged oxidation state is correctly predicted in 34 out of 61 crystal structures; for example, oxidation states V, IV, V, and IV were correctly predicted for the V(1), V(2), V(3), and V(4) atoms in (C 3 H 12 N 2 )­[V 4 O 10 ] (ZOLJEP06), which correspond to the values specified in the original paper.…”
Section: Resultsmentioning
confidence: 58%
“…However, unlike TMC-1, the cell volume of TMC-4 shrinks 0.45% (from 1877.5 Å 3 at 230 K to 1869.0 Å 3 at 450 K) during the bond-switching transition, indicating a negative thermal expansion. [60][61][62]…”
Section: Thermal Analysismentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26] In hybrid materials, at the microscopic level, the changes in physical properties before and after phase transition are closely related to the dynamic motion of molecular dipoles, such as the common ordered-disorder phase transition. [27][28][29][30][31][32][33][34] However, two major challenges arised: (1) how to rationally modify organic cations; (2) building metal halide-inorganic frameworks to obtain multifunctional organic-inorganic hybrid materials. [35][36][37] The molecular design methods might be effec-tive strategy to solve the above issues.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this is expected to be a promising chemical approach for designing multichannel switchable materials, which showing abundant properties: ferroelasticity, piezoelectricity, and SHG responses [17–26] . In hybrid materials, at the microscopic level, the changes in physical properties before and after phase transition are closely related to the dynamic motion of molecular dipoles, such as the common ordered‐disorder phase transition [27–34] . However, two major challenges arised: (1) how to rationally modify organic cations; (2) building metal halide‐inorganic frameworks to obtain multifunctional organic‐inorganic hybrid materials [35–37] .…”
Section: Introductionmentioning
confidence: 99%